2020
DOI: 10.1007/s00223-020-00676-5
|View full text |Cite
|
Sign up to set email alerts
|

High-Level Expression of Alkaline Phosphatase by Adeno-Associated Virus Vector Ameliorates Pathological Bone Structure in a Hypophosphatasia Mouse Model

Abstract: Hypophosphatasia (HPP) is a systemic skeletal disease caused by mutations in the gene encoding tissue-nonspecific alkaline phosphatase (TNALP). We recently reported that survival of HPP model mice can be prolonged using an adeno-associated virus (AAV) vector expressing bone-targeted TNALP with deca-aspartate at the C terminus (TNALP-D 10); however, abnormal bone structure and hypomineralization remained in the treated mice. Here, to develop a more effective and clinically applicable approach, we assessed wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…A further study on the effects of scAAV8-MCK-TNALP-D 10 showed a high doses of 4.5 x 10 12 vg/body injected into the bilateral quadriceps in newborn AKP2−/− mice could increase ALP activity to 20 U/ml in blood and improved the mineralization and bone structure analyzed by micro-CT and radiological analysis. In addition, the histological analysis in growth plate showed normal growth and well-organized cartilage arrangement of AKP2−/− mice treated with 4.5 x 10 12 vg/body [84].…”
Section: Hypophosphatasia (Hpp)-hypophosphatasia (Hpp) Is Characterized By Defective Mineralization Of Bone And/or Teeth In the Presence mentioning
confidence: 89%
“…A further study on the effects of scAAV8-MCK-TNALP-D 10 showed a high doses of 4.5 x 10 12 vg/body injected into the bilateral quadriceps in newborn AKP2−/− mice could increase ALP activity to 20 U/ml in blood and improved the mineralization and bone structure analyzed by micro-CT and radiological analysis. In addition, the histological analysis in growth plate showed normal growth and well-organized cartilage arrangement of AKP2−/− mice treated with 4.5 x 10 12 vg/body [84].…”
Section: Hypophosphatasia (Hpp)-hypophosphatasia (Hpp) Is Characterized By Defective Mineralization Of Bone And/or Teeth In the Presence mentioning
confidence: 89%
“…OVX rats were used as menopausal models to evaluate the promotion of osteogenic differentiation of femoral tissue. Alkaline phosphatase staining has been shown to be strong in the region surrounding the epiphysis because active osteoblast differentiation occurs there [44]. The femurs of sham rats, OVX rats without BCE treatment (control), and OVX rats treated with 3% BCE were stained for alkaline phosphatase.…”
Section: Discussionmentioning
confidence: 99%
“…Whole spine lateral, forelimb and hindlimb radiographs were recorded on a µFX-1000 film (Fujifilm). Imaging conditions were as follows: tube voltage, 25 kV; tube current, 100 µA; exposure time, 30 s ( Nakamura-Takahashi et al, 2020 ). The forelimbs, forefoot fingers and whole spine lateral at 1 year of age were X-ray irradiated and imaged with a Typhoon FLA-7000 scanner (GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%